Ethics of Inclusive Peace and Responsible Governance - Prof. Fr. Davis Panadan CMI; Sini John, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The world faces growing risks from disputes, conflicts, violence, and instability. Building inclusive peace is about much more than ending war. It is about putting in place the institutions and trust that will strengthen the social contract and carry people forward into a peaceful future. It is about resolution of disputes, conflicts, and wars. Inclusion does not mean giving everyone a seat at the negotiating table. It does mean creating opportunities for people with a stake in lasting peace to shape it. Inclusive governance is that the machinery of government is equipped with effective, responsive and accountable institutions capable and empowered to deliver necessary public services to those furthest behind and rebuild public trust in government at the local levels. Governance is most ethically seen in the legal process and the juristic act through which the inclusive peace is achieved. The legal process is the resolution of disputes and conflicts which are actual or occasionally potential, by means of a decision. Pound stresses that law, morals and policy are distinct which can alter the fact that legal decisions are inevitably based on an ideology. Therefore, it is better to face up to this and make a conscious effort to recognize what are the operative values of one’s society and develop the law accordingly, rather than attempt to treat all legal decisions as purely technical exercises in legal logic.
Keywords: Inclusive Peace; Responsible Governance; Sustainable Development Goals (SDGs); Dispute Resolution Institutions; Wartime Governance; Legal Process; Unregulated Conflict